Antihypertensive potential of cis-[Ru(bpy)2(ImN)(NO)]3+, a ruthenium-based nitric oxide donor. (June 2020) - Costa, Paula Priscila Correia; Campos, Rafael; Cabral, Pedro Henrique Bezerra; Gomes, Victor Martins; Santos, Cláudia Ferreira; Waller, Stefanie Bressan; de Sousa, Eduardo Henrique Silva; LOPES, Luiz Gonzaga de França; Fonteles, Manasses Claudino; do Nascimento, Nilberto Robson Falcão
Abstract: The aim of this study was to investigate the antihypertensive properties of cis -[Ru(bpy)2 ImN(NO)] 3+ (FOR0811) in normotensive and in N ω –nitro-L-arginine methyl ester (L-NAME)-induced hypertensive rats. Vasorelaxant effects were analyzed by performing concentration response curve to FOR0811 in rat aortic rings in the absence or presence of 1H-[1, 2, 4]-oxadiazolo-[4, 3, -a]quinoxalin-1-one (ODQ), L-cysteine or hydroxocobalamin. Normotensive and L-NAME-hypertensive rats were treated with FOR0811 and the effects in blood pressure and heart rate variability in the frequency domain (HRV) were followed. FOR0811 induced relaxation in rat aortic rings. Neither endothelium removal nor L-cysteine altered the FOR0811 effects. However, the incubation with ODQ and hydroxocobalamin completely blunted FOR0811 effects. FOR0811 administered intravenously by bolus infusion (0.01–1 mg/bolus) or chronically by using subcutaneous implanted osmotic pumps significantly reduced the mean arterial blood pressure. The effect was long lasting and did not induce reflex tachycardia. FOR0811 prevented both LF and VLF increases in L-NAME hypertensive rats and has antihypertensive properties. This new ruthenium complex compound might be a promising nitric oxide donor to treat cardiovascular diseases. Highlights: Cis -[Ru(bpy)2 ImN(NO)] +3 (FOR0811) has vasorelaxant properties. FOR0811 increases the cGMP in aortic rings of normotensive and hypertensive rats. Neither endothelium removal nor L-cysteine alter the effects of FOR0811. The hypotensive effect of FOR0811 was long without causing tachycardia. FOR0811 prevent low-frequency and very low-frequency increases in hypertensive rats.